2020
DOI: 10.1002/isd2.12166
|View full text |Cite
|
Sign up to set email alerts
|

Mobile financial services in Bangladesh: Understanding the affordances

Abstract: Mobile financial services (MFS) have the potential to impact developing countries by making financial services more accessible. To realize this potential, it is imperative to illuminate why and how people use these new platforms to accomplish their goals. Using affordance theory as a guiding tool, this study aims to uncover the underlying goal directed affordances and actualization techniques used by MFS users in Bangladesh. The data are collected through in‐depth interviews with MFS users and analyzed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…However, users in their attempts to achieve specific goals reveal different latent capabilities of MFS platforms such as accessibility to MFS, ability to self-control, spatial and temporal mobility, ability to disintermediate, self-sustainability and maintainability. Confidentiality, the possibility of communication and the use of various techniques to activate these capabilities are key aspects to consider (Priyo, 2021). The 2023 study also confirmed that perceived risk, relative preference, trust and convenience influence individual tendencies to adopt mobile banking in this order.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, users in their attempts to achieve specific goals reveal different latent capabilities of MFS platforms such as accessibility to MFS, ability to self-control, spatial and temporal mobility, ability to disintermediate, self-sustainability and maintainability. Confidentiality, the possibility of communication and the use of various techniques to activate these capabilities are key aspects to consider (Priyo, 2021). The 2023 study also confirmed that perceived risk, relative preference, trust and convenience influence individual tendencies to adopt mobile banking in this order.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As positive emotion encourages people to feel more freedom to act and reward themselves, this enjoyment triggers their unplanned purchase desire. (Yi Yong Lee et al, 2022) Ummaha Hazra & Asad Priyo (2021), in their paper, "Mobile financial services in Bangladesh: Understanding the affordances," find that MFS has the ability to influence people by making service accessible. The study tried to uncover the underlying goal using the affordance theory for Bangladeshi MFS users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Affordance theory, proposed by Gibson (1979), has emerged as an important theoretical lens in understanding relationships between actors and technology artefacts (Thapa and Sein, 2018; Thapa and Zheng, 2019). Although affordances have been conceptualized in different ways (Lanamäki et al , 2016), the most prominent view in the field of IS is that affordances are action potentials (Hazra and Priyo, 2021; Thapa and Zheng, 2019; Volkoff and Strong, 2017) and therefore generate possibilities of goal accomplishments by users of technology (Markus and Silver, 2008; Strong et al , 2014; Volkoff and Strong, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%